A readiness assessment survey of the adoption of transformational leadership for South African academic libraries in the Gauteng Province - Kunene, Nokuphiwa Glenrose (Library and Information Studies Centre (LISC), 2021)
The study assessed the readiness of the adoption of transformational leadership for South African academic libraries in the Gauteng province. Available literature shows no evidence that assessment has been conducted by academic libraries before the adoption of this leadership style. Academic libraries nationally and internationally are faced with generic challenges like evolutionary technological changes, reduced budget allocations, leadership challenges, and human resources challenges. They are pressured to prove their value to the university due to changing user needs and most academic libraries are faced with a challenge of having to continuously redefine themselves to survive the changing environment. Academic libraries are constantly challenged and must ensure that they have strong leadership that is equipped to face and deal with never-ending challenges. The study surveyed the leadership of the academic libraries in Gauteng. It mainly adopted a descriptive research design. The survey took an exploratory approach to get quality information. The study used a transformative theoretical framework because of its immediate applicability and its focus on the tensions that arise due to unequal power relations. The study is primarily a quantitative study with some qualitative elements as a follow-up to the issues raised in the questionnaire. Quantitative data were analysed with the Statistical Package of Social Sciences (SPSS v25) statistical tool, and descriptive data were coded by assigning labels to codes and using Atlas.ti 8. The study results found that history, politics, and different dynamics related to academic universities influence the leadership style adopted at academic libraries. Several leadership characteristics influence and guide the leadership preference of academic libraries. Two academic libraries indicated that they adopted a participative and transformational leadership style. The libraries have clearly-defined communication channels between the management and staff. However, the creativity and innovation of the staff were affected by other issues. The results also showed that academic libraries must focus more on empowerment, skills development, delegating, and mentoring of their staff to prepare staff for managerial and leadership positions.